Research on the Policy of Introducing Young Talents to Hengqin -- Analysis Based on CGSS2021 - Ren Junlong; Jiang Suni; Wang Ziyan (SHS Web of Conferences)
This paper focuses on the research of policies for introducing young talents to Hengqin. Based on the national survey data CGSS2021, it conducts an in - depth analysis of the influencing factors of youth employment in China. Firstly, the paper expounds on the importance of the youth group to social development, especially their role in the construction of a diversified economy in Macau and the industrial development of the Hengqin - Macau In - depth Cooperation Zone. Subsequently, through the study of a national - scale dataset, it analyzes the impacts of factors such as socioeconomic background, demographic attributes, lifestyle, social trust, and social fairness on youth employment and entrepreneurship. Combining with the analysis of the current situation of the policies for introducing young talents to Hengqin, it puts forward relevant suggestions, such as creating a multi - channel employment promotion matrix, improving youth employment security, and paying attention to policy fairness. This research aims to provide a basis and suggestions for the further improvement of the youth talent policies in the Hengqin - Macau In - depth Cooperation Zone.